Peran Keadilan Prosedural dan Identitas Sosial Dalam Meningkatkan Efektivitas Penerapan E-Tilang Di Jakarta (Analisis Kebijakan) - Ginanjar Maulana Faturohman; Mirra Noor (Mahesa Research Center, 2021)
Some of the violations committed by the driver can lead to several things, which it is counter productive. According to Law No. 2 of 2009 on LLAJ (traffic and road transport) of Article 260 and Article 262 are authorized to take action against violations of traffic is the Indonesian National Police (Polri) and the Civil Servant Investigators. This study aims to assess specifically mengwnai research practice in the application of e-Ticketing system in PMJ scientifically to seek regulatory system is performed by the actors in the implementation of policies and policy arguments or opinions that develop in people who have an impact on the policy of the e-Ticketing. In this study using the method of policy analysis. Policy analysis is a social study which arranges its application in a systematic manner. There are two policies on the implementation of e-Ticketing, namely education and policy. In education there are three criteria, namely: Improving the quality of police officers, forming the image of the police, and educate the public, to inculcate a good identity and obey the law. As for policy namely a rule and punishment from police officers for extortionists or other offenders.